Pengaruh E-wom, Daya Tarik Wisata dan Fasilitas Wisata terhadap Minat Berkunjung Kembali Wisatawan Pantai Indah Bosowa Makassar - leonardo davidsi sipayung; Fitriana; Eureka Try Zarazwanty R Laega (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine how the influence of electronic word of mouth (e-wom), tourist attraction, and tourist facilities on the interest in visiting Indah Bosowa Beach, Makassar. The population in this study was tourists who had visited more than twice in the last year, as many as 150 people. The sampling technique used puporsive sampling. The results of multiple regression tests show that the electronic word of mouth (e-wom) variable has a positive effect on interest in visiting again, obtaining a regression coefficient of 0.149. The tourist attraction variable has a positive effect on return visit interest, with a regression coefficient of 0.150. The tourist facility variable has a positive effect on return visit interest, with a regression coefficient of 0.363. The results of the calculation of the t-test (partial) electronic word of mouth (e-wom) have a significant effect on interest in visiting again, as indicated by the calculation of the t-count value = 2.786> t-table = 1.655 with a significance of 0.004, <0.05. The tourist attraction variable has a significant effect on interest in visiting again, as indicated by the results of the calculation of the tcount value = 2.786> t table = 1.655, with a significant value of 0.005 <0.05. The tourist facilities variable has a significant effect on interest in visiting again, as indicated by the results of the calculation of the tcount value = 2.312> t table = 1.655, with a significant value of 0.002 <0.05. Simultaneous test results (F-test), electronic word of mouth (e-wom) variables, tourist attractions, and tourist facilities have a positive and significant effect on interest in visiting again. This is indicated from the calculation of Fcount = 24.987> Ftable = 2.67 with a significance value of 0.000 <0.05. The results of determination (R2) obtained a value of R2 = 56.5% variable interest in visiting again (Y) is influenced by electronic word of mouth (e-wom), tourist attraction, and tourist facilities, while the remaining 43.5% is influenced by other independent variables not examined in this study.